Good luck system safety (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
It is known that in the republic in practice was Central of the bank interbank payment system of bank customers mainly " large " payments gross ( each one payments according to separate ) calculations based on again performance as well as Clearing system through " retail " payments system of members each one financial operations according to known one period during assembled requirements and obligations pure position determined without done increase opportunity creates It's past period Central of the bank interbank electron payment system improvement , system members and users for advanced technologies based on service show is also specific affairs done increased . Including the Republic Central bank from 2018 starting from new edited " Single representation accounts calculation center ” software complex to practice current done programmatically in the complex payment documents in real time " sessions" mode based on file processing mode to give mechanism to work dropped . Central of the bank interbank thank you system through electron payment documents transition process the following in the scheme statement made by